Hubungan Intensitas Kecanduan Online Games terhadap Prestasi Belajar pada Masa Awal Remaja - Pradana, Reyhan Pradnya; Fanani, Muhammad; Prasetyawati, Arsita Eka (Nexus Kedokteran Komunitas, 2013)
Background: Online games addiction experienced by vulnerable adolescents, especially in early adolescence. In the early teens, they tend to follow what was done by their peers to get an admission in a group. Addiction online games have negative consequences such as lack of sleep, anxiety, apathy correlated to decreased academic achievement. This study aimed to determine the relationship between addiction online games with the level of learning achievement in early adolescence. Methods: this study was a descriptive analytic cross-sectional study approach (cross-sectional) are held from May to July 2012 in the Junior High School 20 Surakarta. Total of 60 subjects sampled by simple random sampling method. Junior High School 20 students Surakarta eighth grade were asked to fill Youngs Diagnostic Questionnaire (YDQ) Lie Scale and the Minnesota Multiphasic Personality Inventory (MMPI-L). Data were analyzed using independent t test and Ï2 test. Results: Based on the results obtained from the 31 students who have addiction online games, 26 students have poor academic achievement and 5 students have a good learning achievement. Statistical analysis demonstrated an association between internet addiction with learning achievement levels in the Junior High School 20 Surakarta (p = 0.000). Conclusions: There is a relationship between addiction online games with the level of student achievement in the Junior High School 20 Surakarta. Keywords: addiction online games, the level of academic achievement